Turn a blind eye [large type] - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- William Warwick novels, 2021)
"Newly promoted, Detective Inspector William Warwick, is tasked with a dangerous new line of work--to go undercover and expose corruption at the heart of the Metropolitan Police. Along with constables Rebecca Pankhurst and Nicky Bailey, his team is focused on following Detective Sergeant Jerry Summers, a young officer whose lifestyle exceeds his income. But the investigation risks being compromised when Nicky falls for Summers. As the undercover officers start to draw the threads together, William realizes that the corruption may go deeper, and more of his colleagues might be willing to turn a blind eye"--Page 4 of cover.